ARM BASED ON LEG BLOOD PRESSURES (ABLE-BP): CAN SYSTOLIC LEG BLOOD PRESSURE MEASUREMENTS PREDICT BRACHIAL BLOOD PRESSURE? AN INDIVIDUAL PARTICIPANT DATA META-ANALYSIS. (June 2022) - McDonagh, Sinead; Sheppard, James; Warren, Fiona; Boddy, Kate; Farmer, Leon; Shore, Helen; Williams, Phil; Lewis, Philip; Fordham, A Jayne; Martin, Una; Aboyans, Victor; Clark, Christopher
Abstract : Objective: Hypertension is diagnosed and managed using brachial blood pressures; accurate measurement can be impeded by several temporary or permanent factors, including fractures, presence of vascular access devices, limb deformities and altered muscle tone after stroke. Leg (ankle) blood pressure measurement is a practical alternative, but limited data exist to guide clinicians' interpretation of leg blood pressure values for hypertension diagnosis and treatment. Design and method: Individual participant data meta-analyses were undertaken, using data from 14 studies within the international inter-arm blood pressure difference individual participant data (INTERPRESS-IPD) Collaboration, to 1) determine the relationship between arm and leg systolic blood pressure, 2) develop and validate a multivariable model predicting arm from leg systolic blood pressure, and 3) investigate the prognostic association between leg systolic blood pressure and cardiovascular disease and mortality. Results: Arm and leg systolic blood pressure data existed for 33, 710 individuals (mean age: 58 years, mean arm systolic/diastolic blood pressure at baseline: 138/80 mmHg, 45% female). Mean leg systolic blood pressure was 12.0 (95% CI, 8.8 to 15.2) mmHg higher than arm systolic blood pressure. The multivariable model derived to predict highest arm from highest leg systolic blood pressure demonstrated excellent performance (area under receiver operating characteristic curves, sensitivity and specificity remained above 0.89, 0.80 and 0.81, respectively, across blood pressure thresholds from 160 to 130 mmHg). Lowest leg systolic blood pressure was a predictor of all-cause mortality and cardiovascular events over a 10-year period. Cardiovascular risk scores were similar for observed arm systolic blood pressure and the highest arm systolic blood pressure predicted from lowest leg systolic blood pressure [Atherosclerotic Cardiovascular Disease Score: 16.73% (12.65) vs 17.17% (12.61), Framingham Score: 19.33% (15.05) vs 19.91% (15.06)]. Conclusions: These results provide a robust evidence-based method for describing the arm-leg systolic blood pressure relationship and estimating individual brachial systolic blood pressure and cardiovascular risk from leg blood pressure measurements using individual participant data. A freely available and easy-to-use web-based calculator has been created to support patients and clinicians in estimating equivalent arm blood pressure when only leg blood pressure measurements and patient characteristics are available.